Peran LKM Sebagai Sarana Input Produksi Garam dan Tenaga Kerja Dalam Usaha Tambak Garam Madura - Jodin Syakatera; Arie Setyo Dwi Purnomo (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to analyze the role of input institutions (microfinance institutions) on salt farmers' businesses in Madura. The microfinance institution sector is one of the input facilities in salt farming processing. Salt farmers often use labor institutions in traditional salt processing. This research also analyzes related input factors such as labor, natural factors, selling prices and land area. From the results of the study using 45 samples of salt farmers from Pamekasan and Sumenep districts. The results of research on capital institutions are very much needed by farmers in salt production activities. Several findings indicate that the role of informal institutions in the aspect of capital for investment and operating costs still relies on loans from families and middlemen. In the input aspect of labor providers, the most important aspect is empowerment related to efficient and productive management methods. This is because workers only use traditional techniques in the process of salt field preparation to harvesting. Meanwhile, salt farming technology is advancing, so it is necessary to modernize tools and soft skills for labor institutional input in order to be able to increase salt production.